(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-3-196-203 The purpose of the article was a scientific understanding of a number of effective technologies of the Soviet propaganda in the context of the issue of the formation of Russian PR and its continuity with the domestic experience of communication activities. The author substantiates the idea that propaganda with an obvious ideological orientation in the Soviet Union represented a structured systematic work based on the scientific knowledge and having a mass character. The “symbolic elite” played a special role in the process of influencing the mass consciousness, including manipulating it, thanks to its authority, ensuring the effective promotion of the official ideology. Anti-crisis PR in the Soviet Union was concentrated in the space of foreign and domestic policy and was mainly based on “soft power” technologies. At the same time, during military events, the propaganda system, which was given the most important meaning in the policy of the Soviet state, strengthened the techniques of mythologization and symbolization, creating images of leaders, Soviet soldiers and the enemy (respectively, positive and negative). In this case, we can discuss the formation of Spin Doctor technologies. In general, the author of the paper believes that certain technologies of the Soviet propaganda, primarily of a civil and patriotic orientation, were quite effective and can be implemented in modern mass communications with a certain adaptation to the sociopolitical realities of the Russian state. Key words: Soviet propaganda, public relations, mass communication, “soft power”, anti-crisis PR, mass media